FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MENJUAL HASIL PANEN DALAM BENTUK GABAH KEPADA TENGKULAK DI DI DESA MEKARSARI KECAMATAN MUARA TELANG (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2022)
ABSTRACTThis study aims to determine the influence of the factors in the decision of farmers to sell their crops in the form of unhulled rice to middlemen, namely the effect of the number of family members on the farmers 'decision to sell their crops in the form of unhulled rice to middlemen, the effect of dependence on middlemen on farmers' decisions to sell their crops in the form of unhulled rice middlemen and the effect of the amount of production on farmers' decisions to sell their crops in the form of unhulled rice to middlemen. This research was conducted in Mekarsari Village, Muara Telang District, Banyuasin Regency from November to January 2021. The research method used was a survey, for sampling using the Simple Random Sampling method. The data collection method used was direct interviews with respondents using a questionnaire that had been prepared beforehand. The data processing used is quantitative. The results showed that there was a significant effect simultaneously or jointly between the number of family members, dependence on middlemen and the amount of production on the farmers' decision to sell their crops in the form of unhulled rice to middlemen, then there was a partially significant effect between the number of family members and dependence on middlemen. against the farmers' decision to sell their crops in the form of unhulled rice to middlemen.ABSTRAKPenelitian bertujuan untuk mengetahui pengaruh faktor-faktor keputusan petani menjual hasil panen dalam bentuk gabah kepada tengkulak yaitu pengaruh jumlah anggota keluarga terhadap keputusan petani menjual hasil panen dalam bentuk gabah kepada tengkulak, Pengaruh ketergantungan kepada tengkulak terhadap keputusan petani menjual hasil panen dalam bentuk gabah kepada tengkulak dan pengaruh jumlah prodksi terhadap keptusan petani menjual hasil panen dalam bentuk gabah kepada tengkulak. Penelitian ini dilaksanakan di Desa Mekarsari Kecamatan Muaratelang Kabupaten Banyuasin pada bulan November 2020 sampai Januari 2021. Metode penelitian yang digunakan adalah Survei, untuk penarikan contoh menggunakan metode Simple Random Sampling. Metode pengumpulan data yang digunakan adalah dengan wawancara langsung kepada responden dengan alat bantu kuesioner yang telah disiapkan sebelumnya. Pengolahan data yang digunakan adalah kuantitatif. Hasil penelitian menunjukan bahwa terdapat pengaruh signifikan secara simultan atau bersama-sama antara jumlah anggota keluarga, ketergantungan kepada tengkulak dan jumlah produksi terhadap keputusan petani menjual hasil panen dalam bentuk gabah kepada tengkulak kemudian terdapat pengaruh signifikan secara parsial antara jumlah anggota keluarga dan ketergantungan kepada tengkulak terhadap keputusan petani menjual hasil panen dalam bentuk gabah kepada tengkulak.